Plasma IL-5 but Not CXCL13 Correlates With Neutralization Breadth in HIV-Infected Children - Roider, Julia; Porterfield, J. Zachary; Ogongo, Paul; Muenchhoff, Maximilian; Adland, Emily; Groll, Andreas; Morris, Lynn; Moore, Penny L.; Ndung'u, Thumbi; Kløverpris, Henrik; Goulder, Philip J. R.; Leslie, Alasdair (Frontiers in Immunology, 2019)
Children may be the optimal target for HIV vaccine development as they generate substantially more frequent and more potent broadly HIV neutralizing antibodies (bnAbs) than adults. Development of a biomarker that correlates with neutralization breadth in this group could function as a powerful tool to facilitate the development of an HIV vaccine. Previously, we observed that this preferential ability in HIV infected children over adults to generate bnAbs is associated with an enrichment of circulating follicular helper T-cells (TFH) with an effector phenotype, and the presence of IL-21 secreting HIV-specific TFH within lymphoid tissue germinal centers (GC). In adults, bnAbs development has been linked with high plasma levels of CXCL13, a chemoattractant for CXCR5-expressing TFH cells to the lymph node GC. We here sought to test this relationship in HIV infected children, but found no relationship between neutralization breadth and CXCL13, the Th2 cytokines IL-4 and IL-13, or the TFH associated factor Activin A. However, we did find an unexpected association between plasma levels IL-5 and bnAb development in these children. Importantly, although CXCL13 correlated with total circulating TFH cells, it was not associated with effector TFH. Additionally, CXCL13 level positively correlated with lower CD4 count, viral load and loss of immune function, implying it is associated with progressive disease rather than HIV-specific GC activity in these subjects. Taken together, our data suggests that IL-5 but not CXCL13 should be evaluated further as a candidate plasma biomarker for HIV neutralization breadth and for monitoring vaccine responses in the pediatric age group.